2019
DOI: 10.1039/c9ay00641a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of microporous polyolefin silica-based paper and cellulose paper substrates utilizing paper spray-mass spectrometry in drug analysis

Abstract: This comparative study proposes an efficient technique by employing a synthetic substrate, which is commercially available, for direct, sensitive, efficient and fast analysis in Paper Spray Mass Spectrometry (PS-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Papers were cut into triangular substrates with rounded lower corners using a universal laser cutter to create substrates with a base of 8 mm and height of 10 mm, leading to a spray tip angle of ∼45°. Other geometries and substrates were tested; however, a rigorous evaluation is not presented here, as other works have characterized the impact of the spray tip angle and substrates on PS-MS performance. Paper substrates were mounted in a stainless steel alligator clip, and a voltage of −3 to −5 kV was applied to the solvent-soaked substrate. The solvent (either HPLC grade methanol or a methanol–chloroform mixture) was continuously supplied to the underside of the substrate with a PEEK delivery tube connected to a syringe pump operating at 20–30 μL min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…Papers were cut into triangular substrates with rounded lower corners using a universal laser cutter to create substrates with a base of 8 mm and height of 10 mm, leading to a spray tip angle of ∼45°. Other geometries and substrates were tested; however, a rigorous evaluation is not presented here, as other works have characterized the impact of the spray tip angle and substrates on PS-MS performance. Paper substrates were mounted in a stainless steel alligator clip, and a voltage of −3 to −5 kV was applied to the solvent-soaked substrate. The solvent (either HPLC grade methanol or a methanol–chloroform mixture) was continuously supplied to the underside of the substrate with a PEEK delivery tube connected to a syringe pump operating at 20–30 μL min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative, another substrate, Teslin ® , was used for the PSI experiments, which allowed HBIW to be detected after the desired reaction time. Cellulose based paper substrates, such as Whatman 1 filter paper, are hydrophilic and have larger pore sizes compared to the Teslin ® substrate which is microporous and hydrophobic 54 , 55 . The reaction mixture was retained on the surface of the Teslin ® substrate due to its hydrophobicity allowing the reaction to occur in the thin film formed on the surface rather than diffusing into the paper when using the Whatman 1 filter paper and reacting in the pores.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, Teslin ® synthetic paper, which composed of micro-porous polyolefin-silica matrix was used as a substrate for depositing sample containing solution droplet. Compared with commonly used cellulose paper, previous work by the authors has indicated that Teslin ® paper allowed the samples to have a larger active signal, resulting in a higher amount of ion formation, and with less interference of molecules from the substrate ( De Silva et al, 2019 ). By comparing with standard RT-PCR tests, the mass spectrometry method achieved a 93.3% sensitivity with an analyzing time of 1 min.…”
Section: Application Of Paper-based Poc Tests For Covid-19mentioning
confidence: 99%